PATHWAYS SHAPING EARLY CHILDHOOD SOCIO-EMOTIONAL COMPETENCE: EDUCATIONAL, SOCIAL INTERACTION, AND SOCIOECONOMIC INFLUENCES (Proceeding of SINERGY, 2026)
This systematic literature review synthesizes empirical evidence on the pathways shaping socio-emotional competence (SEC) in early childhood, with particular attention to educational programs, social interactions, and socioeconomic and cultural contexts. Although SEC has been widely recognized as a foundational aspect of early development, existing studies often examine its determinants in isolation, resulting in a fragmented understanding of how multiple social and contextual factors jointly influence SEC among children aged 3–6 years. To address this gap, the review systematically screened 123 articles retrieved from Scopus and Google Scholar, of which 19 peer-reviewed studies met the inclusion criteria following a PRISMA-guided selection process. The included studies employed diverse methodological approaches, including longitudinal, cross-sectional, experimental, observational, and qualitative designs. The findings indicate that structured Social-Emotional Learning (SEL) programs consistently enhance emotional regulation, empathy, and social competence in early childhood. Beyond formal interventions, high-quality parent–child, teacher–child, and peer interactions emerge as critical proximal processes that support children’s emotional understanding, self-regulation, and interpersonal skills. Moreover, socioeconomic status and cultural norms shape the quality and availability of these interactions, contributing to disparities in SEC development, particularly for children from disadvantaged backgrounds. Overall, the review highlights that early childhood SEC develops through a dynamic and interdependent system involving educational practices, relational experiences, and broader socioeconomic and cultural environments. Future research is encouraged to adopt integrative and culturally sensitive to capture the complexity of SEC development and to inform inclusive interventions that reduce social inequalities while strengthening socio-emotional outcomes in early childhood.